Studi Etnometodologi: Peengendalian Persediaan Beras Bulog - Lupita Sari; Ayudia Sokarina; Adhitya Bayu Suryantara (Jurnal Akademi Akuntansi, 2023)
Purpose: This research aims to interpret rice inventory control by Perum Bulog Regional Office of NTB Methodology/approach: This research uses a qualitative approach with ethnomethodology method. Data collection techniques used observation and interviews. The informants in this study amounted to 4 people consisting of 2 warehouse weighers, 1 OPP implementation staff, and 1 quality management. Findings: The results of this study indicate that the control of rice inventory by Perum Bulog Regional Office of NTB consists of, entry flow, exit flow, and storage of rice quality maintenance in the warehouse. The flow of rice is carried out according to the order from the office in the form of SO (Sell Order) Form through the distribution of disaster relief rice reserves, distribution of class groups, movement activities, and distribution of supply availability and price stability (KPSH). In addition, the flow of rice in the Bulog Regional Office of NTB is carried out in accordance with orders from the office in the form of PO (Purchase Order) Forms through work units (Satker), partnership programs, and through grain and rice processing units (UP-GB). Control of rice inventory at Perum Bulog Regional Office of NTB is carried out in accordance with logistics orders to maintain inventory turnover at the price of government regulations. Practical and Theoretical contribution/Originality: Controlling rice inventory at Perum Bulog Regional Office of NTB using Ethnomethodology methods Research Limitation: It is difficult to arrange informants' schedules to conduct interviews due to many other jobs so that researchers have difficulty when obtaining data